Pelvis Anatomy Tutorial Using Radiological Images - Madeleine J. Marsland; Dunya Tomic; Pamela L. Brian; Michelle D. Lazarus (Association of American Medical Colleges, 2018)
Introduction Improving integration between basic science and clinical application is essential in medical education. Anatomy courses can do this by focusing on medical imaging interpretation. Most imaging textbooks rely on structural identification, which novice learners often struggle to apply to the health care environment, particularly in complex regions like the pelvis, which is multifaceted and differs substantially between sexes. To address this deficit, this resource extends our imaging-based tutorial series. Methods This tutorial was a self-administered PowerPoint incorporating X-ray, computed tomography, and magnetic resonance imaging, which are all often used for the pelvic region, as well as self-quizzing and clinical applications. Using repeated-measures, control/experimental design, the tutorial was evaluated as a review tool for 57 Australian medical students in preclerkship years. Participants were evaluated by a rating self-efficacy scale, knowledge-based testing (multiple-choice, short-answer, and identification questions), and feedback to open-ended questions. Results Results indicate that the tutorial significantly improved direct knowledge (p = .006), as the experimental group's posttutorial scores for direct questions were superior by 21% on average. Significant improvements occurred specifically for direct short-answer and indirect image-identification questions. Discussion These results suggest the tutorial is an effective review tool. While previous tutorials were evaluated as adjunct tools, this tutorial was evaluated post-anatomy teaching with similar results. Students improved in direct and applied anatomy following tutorial exposure. This suggests that the tutorial series comprises valuable review and supplementary materials. None of our tutorials have been evaluated as a sole mechanism for teaching anatomy or imaging.